Peningkatan Kemampuan Pemecahan Masalah Matematik Siswa SMA melalui Pembelajaran Matematika dengan Strategi Kooperatif Tipe STAD - Siswadi, Siswadi (IAIN PADANGSIDIMPUAN, 2019)
This study aims to see how the efforts in improving the mathematical problem solving ability of high school students by learning STAD type cooperative strategies. This research is based on the importance of mathematical problem solving abilities that must be possessed by students, but the reality on the ground that these abilities are still very low. This research is an experiment with a pretest-posttest control group design. This is done in order to find out how much improvement in the ability to solve mathematical problems taught by learning mathematics in STAD type cooperative strategies. For the experimental group, students are taught with STAD type cooperative strategies, while in the control group, students are taught by direct learning. The population of this study was high school students, while the sample was students of class XI IPA of Laksamana Martadinata Medan Private High School. Five classes were randomly selected, class XI IPA 3 class as the experimental class and XI IPA 1 as the control class. The instrument used in the form of problem solving problems. Based on the results of the analysis, it can be concluded that: 1) there is a mean difference between students who are taught with STAD type cooperative strategies and those who are in direct learning. 2) Improvement of students' mathematical problem solving abilities that get cooperative learning type STAD gets direct learning ineffective.